Co-creating Value along the Agri-Food Chains through Efficient Process Management – Using Atlassian Tools - Marius CONSTANTIN; Simona Roxana PATARLAGEANU; Mihai DINU; Iuliana Denisa RADULESCU (Communications of International Proceedings, 2021)
Agriculture, the agri-food system and all the processes that contribute to the generation of different forms of value along the agri-food chains have become increasingly globalized and digitized. The global agri-food value chain does not provide only farmers with the opportunity for generating added-value along the chain, but rather it enhances the value co-creation potential by allowing an easy integration of other global links into the chain – links that might not carry out activities related to the agri-food industry explicitly, such as the processing and marketing of agri-food products. In this regard, some modern chain links have a specific managerial orientation, which corroborated with an affinity for intelligent information technology systems act as vectors for maximizing the value generation potential along the agri-food value chain through efficient process management. The emergence of the globally-connected internet-based cloud infrastructures through information systems involves a change regarding the value creation paradigm in the agri-food chains. Modern chain links contribute to the value co-creation processing if analyzed through the lens of the joint actions carried out by both agri-food producers and the enterprises managing their production and marketing flows using software, which happen in the digital space. The objective of this research paper was to explore the process of co-creating value along the agri-food value chains through efficient process management by using Atlassian tools.
Keywords: Global agri-food value; value co-creation; process management; Confluence; Trello; Atlassian